Enhanced nutritional profiles through increased nutrition fact labels usage during the pandemic era - Cho, Jung Min; Jeong, Sarang (Journal of nutrition and health, 2025)
Purpose: Nutrition fact labels (NFLs) provide essential information on the nutritional contents of food packages. This study examined whether increased NFL usage during the pandemic would lead to improved energy and nutrient intakes in the pre-(2019), acute (2020), and chronic (2021) pandemic years. Methods: A cross-sectional study was conducted using the weighted multiyear method and 24-hour dietary recall from the Korea National Health and Nutrition Examination Survey (KNHANES). Healthy adults were categorized into two groups: those influenced by NFL information (affected group) and those unaware of NFLs (unaware group). Results: There was a significant decline in the proportion of adults unaware of NFLs from 2019 to 2021, with awareness increasing more notably among females. Among the affected group, reductions were observed in daily intake of energy, carbohydrates, sodium, fat, saturated fatty acids (in males), and sugars (in females) by 2021. For males, mean energy intake decreased from 2,373.4 kcal/day in 2019 to 2,088.9 kcal/day in 2021; for females, from 1,695.4 kcal/day to 1,525.2 kcal/day. Carbohydrate intake dropped from 300.1 g/day to 265.1 g/day in males, and from 238.1 g/day to 212.2 g/day in females. Sodium intake declined from 4,258.7 mg/day to 3,479.3 mg/day in males, and from 2,834.7 mg/day to 2,557.1 mg/day in females. These trends suggest that increased awareness of NFLs may have contributed to improved dietary behaviors during the COVID-19 pandemic period. Conclusion: The impact of NFL use during the pandemic was associated with healthier diets after the pandemic in healthy Korean adults. KCI Citation Count: 0